"Changing beyond Recognition"?: Reimagining the future of smallholder farming systems in the context of climate change. Issue 115 (October 2020) - Kweka, Opportuna L.; Ouma, Stefan
Abstract: We use the case of Northern Tanzania to put empirical flesh on the idea of diverse economies. We advance the idea that smallholder production systems offer ontological and practical resources to envision and perform more viable African rural futures, potentially with important lessons for the rest of the world.